Posisi Buton dalam Arus Sejarah Indonesia - Mulyanto, Heru (Humanis, 2022)
Buton is a local kingdom that has not been widely discussed in Indonesian history. This sultanate has a uniqueness that is rarely owned by other sultanates in the archipelago. One of these uniquenesses is the ties of cooperation between Buton and the VOC in many fields. Because of this, Buton is often considered a traitorous sultanate. This study was written to map the position of the Sultanate of Buton in terms of economy, politico-government, trade, defense, and diplomacy (including relations with the VOC) in Indonesian history. The critical history method was used in writing this article by using related research literature sources. It was concluded that the Buton government was in a unique position compared to other sultanates because the sultan was elected by the people and was not hereditary. Meanwhile, Buton's shipping and trade strategy remained at the point of Nationalism even though cooperation with the VOC was established here. Buton's government structure indicates that the position of this sultanate is at a modern stage compared to the sultanates in Java and Kalimantan.